Default resolution and access to fresh credit in an emerging market - Hussain, Inayat; Durand, Robert; Harris, Mark N. (Elsevier BV, 2016)
We examine loan defaults by firms and identify the factors that influence both the default resolution process and firms' access to fresh credit after firms exit default. Using a dataset of all commercial loans made in Pakistan from 2006 to 2013, we find an important role for collateral. Collateral expedites both the default resolution process and access to fresh credit after exiting default. Higher interest rates increase the default duration. Relationships with multiple lenders as well as those with multiple branches of one lender are associated with obtaining fresh credit at the post default stage.